Effects of Adaptation on Biodegradation Rates in Sediment/Water Cores from Estuarine and Freshwater Environments - Spain, Jim C. (1980)
Experiments were devised to determine whether exposure to xenobiotics would cause microbial populations to degrade the compounds more rapidly during subsequent exposures. Studies were done with water/sediment systems (ecocores) taken from a salt marsh and a river. Systems were tested for adaptation to the model compounds methyl parathion and p-nitrophenol. (14)CO(2) released from radioactive parent compounds was used as a measure of mineralization. River populations preexposed to p-nitrophenol at concentrations as low as 60 μg/liter degraded the nitrophenol much faster than did control populations. River populations preexposed to methyl parathion also adapted to degrade the pesticide more rapidly, but higher concentrations were required. Salt marsh populations did not adapt to degrade methyl parathion. p-Nitrophenol-degrading bacteria were isolated from river samples but not from salt marsh samples. Numbers of nitrophenol-degrading bacteria increased 4 to 5 orders of magnitude during adaptation. Results indicate that the ability of populations to adapt depends on the presence of specific microorganisms. Biodegradation rates in laboratory systems can be affected by concentration and prior exposure; therefore, adaptation must be considered when such systems are used to predict the fate of xenobiotics in the environment.